Green supply chain management strategy and financial performance in the shipping industry - Alexandrou, Stelios; Panayides, Photis; Tsouknidis, Dimitris; Alexandrou, Andria E. (My University, 2021)
This study empirically examines the relationship between green supply chain management (GSCM) strategy and financial performance for shipping firms. We collect global data from 289 shipping firms and apply cluster analysis and analysis of variance (ANOVA) to test the research hypotheses. We cluster shipping firms according to their level of GSCM strategy adoption, which ranges from reactive to proactive. We find that shipping firms with a proactive GSCM strategy perform better financially. The findings of this study can contribute to shipping firms’ environmental management strategy decisions and help tackle environmental problems while improving their financial outcome. This paper provides a discussion of managerial and theoretical implications and recommends future research directions.
Keywords: Green supply chain management; Proactive green strategy; Environmental management strategy; Green shipping management practices; Financial performance; Shipping